2016
DOI: 10.1038/nplants.2016.150
|View full text |Cite
|
Sign up to set email alerts
|

Genomic prediction contributing to a promising global strategy to turbocharge gene banks

Abstract: The 7.4 million plant accessions in gene banks are largely underutilized due to various resource constraints, but current genomic and analytic technologies are enabling us to mine this natural heritage. Here we report a proof-of-concept study to integrate genomic prediction into a broad germplasm evaluation process. First, a set of 962 biomass sorghum accessions were chosen as a reference set by germplasm curators. With high throughput genotyping-by-sequencing (GBS), we genetically characterized this reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
182
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(198 citation statements)
references
References 46 publications
9
182
0
Order By: Relevance
“…Heritabilities and CV1 prediction accuracy for GY and PH in our study were similar to those found in previous studies in sorghum (Fernandes, Dias, Ferreira, & Brown, 2018; Hunt et al., 2018; Yu et al., 2016). Similar heritabilities and r for flowering time, PL, PH, and GN have previously been reported in a rice diversity panel (Guo et al., 2014).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Heritabilities and CV1 prediction accuracy for GY and PH in our study were similar to those found in previous studies in sorghum (Fernandes, Dias, Ferreira, & Brown, 2018; Hunt et al., 2018; Yu et al., 2016). Similar heritabilities and r for flowering time, PL, PH, and GN have previously been reported in a rice diversity panel (Guo et al., 2014).…”
Section: Discussionsupporting
confidence: 91%
“…The SRT prediction method also showed smaller r for pairwise prediction results for the panicle architecture traits than other traits. Yu et al (2016) previously observed that race as a predictor explains higher variation in predicted values of biomass traits than actual phenotypic values in sorghum, suggesting that under the presence of similar racial structure in training and validation populations, the accuracy of genomic prediction might have been inflated as a result of overemphasis on racial differences (Brown, 2016). Our approach of decomposition of covariances into conditional expectations due to race could be used in dissection of impact of population structure in CV accuracy from stratified and random sampling methods in diverse as well as breeding populations.…”
Section: Crop Sciencementioning
confidence: 99%
“…Furthermore, our results correspond with studies by Gorjanc et al (2016) and Yu et al (2016) in that it seems possible to achieve predictive accuracies high enough to advance selection in breeding programs using diverse accessions from within genetic resource collections, but that training population sizes that are larger than those retained in many core collections are likely required to achieve useable predictions. The goal of using 10 to 20% of a collection to represent the genetic diversity of that collection for complex traits may be unrealistic.…”
Section: Discussionsupporting
confidence: 86%
“…The other 75 additions will presumably be more unrelated to these selection candidates, leading to the intermediate average relationship (Figure 5, A and B) and often lower persistence of LD phase (Figure 5, G and H); however, these training population additions may provide information for more reliable predictions. In a study where the training population was a subset of a larger population, Yu et al (2016) found that individuals in the validation population ( i.e. , selection candidates) with the highest and lowest predicted genotypic values had the greatest upper bound for the reliability of those predictions (Karaman et al 2016).…”
Section: Discussionmentioning
confidence: 99%